2007
DOI: 10.1007/s10827-007-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic bursting enhances the robustness of a neural network model of sequence generation by avian brain area HVC

Abstract: Avian brain area HVC is known to be important for the production of birdsong. In zebra finches, each RA-projecting neuron in HVC emits a single burst of spikes during a song motif. The population of neurons is activated in a precisely timed, stereotyped sequence. We propose a model of these burst sequences that relies on two hypotheses. First, we hypothesize that the sequential order of bursting is reflected in the excitatory synaptic connections between neurons. Second, we propose that the neurons are intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 77 publications
(146 reference statements)
4
104
1
Order By: Relevance
“…(A similar result was announced independently by Jin and collaborators [7], who studied a more complicated model. We discuss this preprint briefly in Section IV below.)…”
Section: Introductionsupporting
confidence: 73%
“…(A similar result was announced independently by Jin and collaborators [7], who studied a more complicated model. We discuss this preprint briefly in Section IV below.)…”
Section: Introductionsupporting
confidence: 73%
“…Previously proposed models of HVC were constructed using strong excitatory inputs linking active ensembles of neurons into a purely feedforward network (Li and Greenside, 2006;Jin et al, 2007). Experimentally, intracellular recordings in HVC of zebra finches (Long et al, 2010) has supported the idea that a chain of synaptically connected neurons drives the motor sequence of singing.…”
Section: Intracellular Recordings Provide a Window Into A Motor Sequementioning
confidence: 99%
“…In the mammalian motor cortex, it has been shown that the process of motor learning is associated with a sparsening (Komiyama et al, 2010) and temporal sharpening (Masamizu et al, 2014;Peters et al, 2014) of neural activity as learned sequences emerge. In the juvenile songbird, the activity of single HVC premotor neurons has not yet been described, but the possibility exists that multiple premotor links may be useful for exploring a range of potential vocal behaviors during song learning.…”
Section: Intracellular Recordings Provide a Window Into A Motor Sequementioning
confidence: 99%
“…A leading candidate is a ''synfire'' chain comprising HVC RA neurons linked together by their local excitatory connections, an idea incorporated into modeling studies of central song patterning networks (Li and Greenside 2006;Jin et al 2007). In fact, the axons of HVC RA neurons extend local collaterals before exiting HVC, forming excitatory synapses with other HVC RA cells, as well as interneurons and HVC X cells, providing a potential substrate for a synfire chain (Mooney 2000;Mooney and Prather 2005).…”
Section: Song Motor Codes In the Smpmentioning
confidence: 99%